Monitoring of the Corporate Competitiveness Effect of Tourism Support - Nagy, Tünde; Darabos, Éva (International Journal of Engineering and Management Sciences, 2020)
Today the tourism is without doubt strategic of importance in the world. In Hungary’s case can be related, that contributes to the performance of the economy largely, and its role is very important in the employment, too. Because of national economic weight it is suitable to analysing, but for the sake of complexity the consideration of economic performance, competitiveness exceptionally complicated task. The two sections are attached most directly, the performace is measurable through the accomodation service and hospitality. Present study does not intend to measure the performance of whole tourism section, the aim is from a corporate side, measure the corporate competitiveness from accountancy datas, the examination of part. The object of the actual examination is monitoring of the profitability effect of tourism supports through the example of 8 companies.